42. A Pharmacist-Led Intervention to Decrease Anaerobic Coverage for Hospitalized Patients with Community-Acquired Pneumonia. (31st December 2020) - Enzmann, Maxx O; Pagels, Courtney M; Perry, Emily J; Jones, Justin; Carson, Paul
Abstract: Background: Community-acquired pneumonia (CAP) is frequently mis-categorized as aspiration pneumonia, prompting the addition of anaerobic coverage to the antibiotic regimen. In our institution, this usually takes the form of adding metronidazole to ceftriaxone. The 2019 American Thoracic Society and Infectious Diseases Society of America CAP guidelines recommend anaerobic coverage only for hospitalized patients with a suspected lung abscess or empyema. The objective of this study was to determine if a pharmacist-led workflow could increase adherence to the 2019 CAP guideline recommendations by limiting anaerobic coverage to those rare occasions. Methods: The hospital antimicrobial stewardship committee approved a pharmacist workflow and guidance document which outlines criteria to evaluate appropriateness of anaerobic coverage for hospitalized patients with CAP and no other indications for antibiotics. If anaerobic coverage is not indicated, the pharmacist submits a standardized message to the treating provider via the electronic medical record, recommending discontinuation of metronidazole. This workflow was implemented on October 3, 2019. Metronidazole days of therapy (DOT) per 1000 patient days in quarters 1 through 4 of 2019 and quarter 1 of 2020 were collected as well as percent acceptance of documented pharmacist interventions from October 3, 2019 until March 31, 2020. Results: Between October 3, 2019 and March 31, 2020, a total of 221 interventions were made by pharmacists to discontinue metronidazole in hospitalized CAP patients where anaerobic coverage was not indicated. Out of those 221 interventions, 164 (74%) were accepted by providers and only 57 (26%) were rejected. The DOT per 1000 patient days of metronidazole was assessed for the three quarters prior to our intervention and the two quarters after the intervention. Compared to the three quarters prior, metronidazole DOT per 1000 patient days decreased by 26.6% for the two quarters following implementation of the pharmacist-led intervention (Figure 1). Figure 1: Metronidazole DOT per 1000 patient days from January 1, 2019 through March 31, 2020. Vertical line indicates when pharmacist workflow was implemented. Conclusion: A pharmacist antimicrobial stewardship intervention at our institution increased adherence to CAP guidelines and decreased unnecessary antibiotic exposure in hospitalized CAP patients when anaerobic coverage was not indicated. Disclosures: All Authors : No reported disclosures